Novel assays for detection and characterization of soluble proteases - Goyal, Garima (Nanyang Technological University, 2021)
Protease belongs to a class of enzymes that catalyze the hydrolysis of peptide bonds between amino acids, within peptides and proteins. It is involved in cellular homeostasis by performing functions as primary as food degradation to regulation of other proteins by their precise cleavage. Little aberrations in its expression can lead to the development of different diseases. Hence, the differential expression levels of protease offer opportunities to employ it as a disease biomarker.